Cosmological constraints from the tomographic cross-correlation of DESI Luminous Red Galaxies and Planck CMB lensing. Issue 2 (3rd February 2022) - White, Martin; Zhou, Rongpu; DeRose, Joseph; Ferraro, Simone; Chen, Shi-Fan; Kokron, Nickolas; Bailey, Stephen; Brooks, David; García-Bellido, Juan; Guy, Julien; Honscheid, Klaus; Kehoe, Robert; et al.
Abstract: We use luminous red galaxies selected from the imaging surveys that are being used for targeting by the Dark Energy Spectroscopic Instrument (DESI) in combination with CMB lensing maps from the Planck collaboration to probe the amplitude of large-scale structure over 0.4 ⩽  z  ⩽ 1. Our galaxy sample, with an angular number density of approximately 500 deg -2 over 18, 000 sq.deg., is divided into 4 tomographic bins by photometric redshift and the redshift distributions are calibrated using spectroscopy from DESI. We fit the galaxy autospectra and galaxy-convergence cross-spectra using models based on cosmological perturbation theory, restricting to large scales that are expected to be well described by such models. Within the context of ΛCDM, combining all 4 samples and using priors on the background cosmology from supernova and baryon acoustic oscillation measurements, we find S 8  = σ8 (Ωm /0.3) 0.5  = 0.73 ± 0.03. This result is lower than the prediction of the ΛCDM model conditioned on the Planck data. Our data prefer a slower growth of structure at low redshift than the model predictions, though at only modest significance.